2019
DOI: 10.1073/pnas.1908128116
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous regulation of group 3 innate lymphoid cells by nongastric Helicobacter species

Abstract: Intestinal innate lymphoid cells (ILCs) contribute to the protective immunity and homeostasis of the gut, and the microbiota are critically involved in shaping ILC function. However, the role of the gut microbiota in regulating ILC development and maintenance still remains elusive. Here, we identified opposing effects on ILCs by two Helicobacter species, Helicobacter apodemus and Helicobacter typhlonius, isolated from immunocompromised mice. We demonstrated that the introduction of both Helicobacter species ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…These species activated ILCs but negatively regulated the proliferation of group 3 RORγt + ILCs that are crucial for host immunity and inflammation. 95 Type 3 ILCs mediate immune surveillance of microbiota configuration to facilitate early colonization resistance through a transcriptional regulator ID2-dependent regulation of IL-22. 96 NCR + ILC3 cells were demonstrated to be essential for maintaining cecal homeostasis in mice during Citrobacter rodentium infection.…”
Section: Interaction Between Microbiota and Immune System In Homeostasismentioning
confidence: 99%
“…These species activated ILCs but negatively regulated the proliferation of group 3 RORγt + ILCs that are crucial for host immunity and inflammation. 95 Type 3 ILCs mediate immune surveillance of microbiota configuration to facilitate early colonization resistance through a transcriptional regulator ID2-dependent regulation of IL-22. 96 NCR + ILC3 cells were demonstrated to be essential for maintaining cecal homeostasis in mice during Citrobacter rodentium infection.…”
Section: Interaction Between Microbiota and Immune System In Homeostasismentioning
confidence: 99%
“…The interplay of ILCs and the microbiota in mucosal infections plays a determining role in intestinal immunity. Bostick et al 16 showed that enteric Helicobacter species promoted opposing effects on ILCs in immunocompromised mouse models. Both H. apodemus and Helicobacter typhlonius activated ILCs and induced gut inflammation, but negatively regulated proliferation of ILC3s (type 3 ILCs) involved in the innate immune response to extracellular pathogen and diminished their proliferative capacity.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Both H. apodemus and Helicobacter typhlonius activated ILCs and induced gut inflammation, but negatively regulated proliferation of ILC3s (type 3 ILCs) involved in the innate immune response to extracellular pathogen and diminished their proliferative capacity. This dichotomous regulation of ILCs by Helicobacter species in immunocompromised mice constitutes a model for future investigations of the host‐microbe interactions that maintain ILC3s in the intestine 16 and opens new fields of investigation regarding the virulence factor(s) of these enteric Helicobacters that may influence the maintenance of ILC3s in the intestine.…”
Section: Animal Modelsmentioning
confidence: 99%
“…negatively regulated RORγt + ILC3, especially T-bet + ILC3, and reduced their proliferative capacity. In contrast, wild type mice could sustain ILC3 function in the presence of Helicobacter spp., indicating an interaction between ILCs and effector T cells [ 112 ]. Hepworth and colleagues recently reported that ILC3 suppress the T cell-dependent IgA response to H. typhlonius in order to preserve the microbial niche [ 76 ].…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%